2020
DOI: 10.1200/jco.2020.38.15_suppl.9005
|View full text |Cite
|
Sign up to set email alerts
|

CTONG1104: Adjuvant gefitinib versus chemotherapy for resected N1-N2 NSCLC with EGFR mutation—Final overall survival analysis of the randomized phase III trial 1 analysis of the randomized phase III trial.

Abstract: 9005 Background: ADJUVANT-CTONG1104, a randomized phase 3 trial showed adjuvant gefitinib treatment significantly improved disease-free survival (DFS) vs standard doublet chemotherapy in patients (pts) with epidermal growth factor receptor ( EGFR) mutation-positive resected stage II-IIIA (N1-N2) non-small-cell lung cancer (NSCLC). 5-year survival rate of N1N2 were 38%-50% in IASLC staging system. Here, we present the final overall survival (OS) results from the study. Methods: From Sep 2011 to April 2014, 222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…The CTONG1104/ADJUVANT trial is a phase 3 study that compared the standard cisplatin-vinorelbine chemotherapy to gefitinib, a first-generation EGFR TKI in fully resected stage II to IIIA EGFR mutant NSCLC [ 12 ]. Chemotherapy was administered for four cycles, while gefitinib was given until progression for up to two years.…”
Section: Epidermal Growth Factor Receptor (Egfr) Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CTONG1104/ADJUVANT trial is a phase 3 study that compared the standard cisplatin-vinorelbine chemotherapy to gefitinib, a first-generation EGFR TKI in fully resected stage II to IIIA EGFR mutant NSCLC [ 12 ]. Chemotherapy was administered for four cycles, while gefitinib was given until progression for up to two years.…”
Section: Epidermal Growth Factor Receptor (Egfr) Mutationsmentioning
confidence: 99%
“…While the HR of DFS is certainly impressive, there is much controversy about whether these immature data should lead to a change in practice, as the real question is whether patients will live longer if treated earlier. Furthermore, at the ASCO 2020, the final analysis of the CTONG1104/ADJUVANT trial was presented, showing that treating EGFR positive patients with EGFR TKI delayed the relapse but did not translate into OS benefit [ 12 ]. Moreover, the ADAURA trial doesn’t address the question about the importance and need for adjuvant chemotherapy in these patients, as the majority of them received it before being randomized in the trial.…”
Section: Epidermal Growth Factor Receptor (Egfr) Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Updated OS analysis with a median follow-up of 76.9 months showed no difference between groups: 75.5 months for gefitinib and 79.2 months for chemotherapy, HR 0.96, p = 0.823. The 3 and 5 year OS rates were 68.6% and 53.8% for gefitinib and 67.5% and 52.4% for vinerolbine plus cisplatin, respectively [ 47 ]. The EVAN phase II study compared adjuvant erlotinib with cisplatin and vinerolbine in 102 patients with resected stage IIIA EGFR-positive NSCLC.…”
Section: Egfr Monotherapy As Adjuvant Therapy In Early-stage Diseamentioning
confidence: 99%
“…Currently, the only mature OS data we have with tyrosine kinase inhibitors (TKI) for the EGFR-mutated NSCLC come from the above-mentioned CTONG1104 phase III trial which showed a nonsignificant HR for death of 0.92 (95% CI 0.62-1.36; p=0.674) for gefitinib versus cisplatin-vinorelbine, corresponding to a 2.1% non-significant survival improvement in favour of chemotherapy 4 .…”
mentioning
confidence: 99%